Microwave Assisted Synthesis of 1-[5-(Substituted Aryl)-1H-Pyrazol-3-yl]-3,5-Diphenyl-1H-1,2,4-Triazole as Antinociceptive and Antimicrobial Agents - Khanage, Shantaram Gajanan (Tabriz University of Medical Sciences, 2014)
Purpose: An efficient technique has been developed for microwave assisted synthesis of 1-[5-(substituted aryl)-1H-pyrazol-3-yl]-3,5-diphenyl-1H-1,2,4-triazole as antinociceptive and antimicrobial agents. Methods: The desired compounds (S(1)-S(10)) were synthesized by the microwave irradiation via cyclization of formerly synthesized chalcones of 3,5-diphenyl-1H-1,2,4-triazole and hydrazine hydrate in mild acidic condition. All newly synthesized compounds were subjected to study their antinociceptive and antimicrobial activity. The analgesic potential of compounds was tested by acetic acid induced writhing response and hot plate method. The MIC values for antimicrobial activity were premeditated by liquid broth method. Results: The compounds S(1), S(2), S(4), S(6) and S(10) were found to be excellent peripherally acting analgesic agents when tested on mice by acetic acid induced writhing method and compounds S(3), S(6) and S(1) at dose level of 100 mg/kg were exhibited superior centrally acting antinociceptive activity when tested by Eddy’s hot plate method. In antimicrobial activity compound S(10) found to be broad spectrum antibacterial agent at MIC value of 15.62 µg/ml and compound S(6) was exhibited antifungal potential at 15.62 µg/mL on both fungal strains. Conclusion: Some novel pyrazoles clubbed with 1,2,4-triazole derivatives were synthesized and evaluated as possible antimicrobial, centrally and peripherally acting analgesics.